The open space design of Istvántelek Head Depot - Pécsi, Máté (4D Journal of Landscape Architecture and Garden Art, 2007)
Nowdays it's pretty obvious, that the revitalisation of brownfields in Budapest should be a key project to our national Capital. The brownfield belt of Budapest is a huge area, with a lot of possibilities. In the 80s, and 90s, the large State industrial sites mostly finished their production, they went broke. But these areas are still in the heart of the city, they are one important part of the complex urban fabric.
Keywords: open space; revitalisation; Istvántelek; train